Computer-Generated Radiographic Measurements of Distal Radius Fractures: Does It Help With Decision Making? - Davidson, Amit; Feldman, Guy; Mosheiff, Rami; Suna, Avigail; Joskowicz, Leo; Weil, Yoram A. (The Journal of hand surgery (American ed.), 2024)
Operative management of distal radius fractures (DRFs) has become increasingly common. Age, activity levels, and comorbid conditions are major factors influencing the treatment decision, although operative indications are still controversial. Radiographic parameters (RPs), such as radial inclination, dorsal tilt, and articular step-off, can provide objective support for effective decision making. However, manual measurement of RPs may be imprecise and subject to inconsistency. To address this problem, we developed custom software of an algorithm to automatically detect and compute 6 common RPs associated with DRF in anteroposterior and lateral radiographs. The aim in this study was to assess the effect of this software on radiographic interobserver variability among orthopedic surgeons. Our hypothesis was that precise and consistent measurement of RPs will improve radiographic interpretation variability among surgeons and, consequently, may aid in clinical decision making. Thirty-five radiograph series of DRFs were presented to 9 fellowship-trained hand and orthopedic trauma surgeons. Each case was presented with basic clinical information, together with plain anteroposterior and lateral radiographs. One of the 2 possible treatment options was selected: casting or open reduction with a locking plate. The survey was repeated 3 weeks later, this time with computer-generated RP measurements. Data were analyzed for interobserver and intraobserver variability for both surveys, and the interclass coefficient, kappa value, was calculated. The interobserver reliability (interclass coefficient value) improved from poor to moderate, 0.35 to 0.50, with the provided RP. The average intraobserver interclass coefficient was 0.68. When participants were assessed separately according to their subspecialties (trauma and hand), improved interobserver variability was found as well. Providing computed RPs to orthopedic surgeons may improve the consistency of the radiographic judgment and influence their clinical decision for the treatment of DRFs. Orthopedic surgeons’ consistency in the radiographic judgment of DRFs slightly improved by providing automatically calculated radiographic measurements to them.